Study on the effect of phosphorus on anti-softening performance of oxygen-free copper - Zihao Zhang; Haitao Liu; Yunxiao Hua; Baofeng Zhang; Zhenguo Hou; Weiqiang Li; Kexing Song (Journal of Materials Research and Technology)
This study investigates the preparation of oxygen-free copper with varying phosphorus (P) content through vacuum melting and examines the influence of P on the mechanical properties, softening resistance, and microstructure of the material. The results indicate that as the P content increases (≤1400 wt ppm), the grain size of the oxygen-free copper becomes progressively finer, resulting in significant improvements in microhardness and softening temperature. Notably, when the P content reaches 1400 wt ppm, the microhardness and softening temperature (121.4 HV, 341.35 °C) are markedly superior compared to those with a P content of 0.01 wt ppm (101.89 HV, 210.31 °C). Electron backscatter diffraction (EBSD) was used to analyze the samples before and after softening annealing, and it was found that the P element inhibited the recrystallization behavior of oxygen-free copper by hindering dislocation movement, thereby achieving the effect of increasing the softening temperature. Transmission electron microscopy (TEM) results further demonstrate that annealing softening in P-containing oxygen-free copper (1400 wt ppm) predominantly occurs through discontinuous dynamic recrystallization (DDRX) and twinning dynamic recrystallization (TDRX), thereby altering the recrystallization mechanism of the copper.